The Caste System in Pramoedya Ananta Toer’s Novel Bumi Manusia - Zukhaira Hayati; Muhammad Fatih Suhadi (Universitas Islam Sumatera Utara, 2026)
This study examines the portrayal and implications of the caste system in Bumi Manusia by Pramoedya Ananta Toer. Set during Dutch colonial rule in nineteenth-century Indonesia, the novel presents a nuanced depiction of how hierarchical social structures shape individual identities, relationships, and broader societal interactions. Employing a qualitative descriptive method, this research focuses on close textual analysis to explore key aspects of the caste system within the narrative. These include its structural elements, the positioning of characters within different social strata, and its role in sustaining inequality and power relations. The findings show that colonial practices imposed rigid hierarchies that dehumanized indigenous people by constructing them as inherently inferior. Such conditions not only reinforced social divisions but also influenced how individuals perceived themselves and others within the colonial order. In response, the colonized developed forms of resistance that extended beyond physical confrontation. They utilized intellectual, moral, and cultural strategies to challenge colonial authority and assert their dignity. In other words, this study demonstrates that the novel not only reflects the socio-cultural realities of colonial Indonesia but also offers a critical perspective on the lasting impact of caste and colonial hierarchies, particularly in shaping resistance, identity, and emerging nationalist consciousness.